TGFβ2 Induces the Soluble Isoform of CTLA-4 – Implications for CTLA-4 Based Checkpoint Inhibitor Antibodies in Malignant Melanoma - Khanolkar, Rahul C.; Zhang, Chu; Al-Fatyan, Farah; Lawson, Linda; Depasquale, Ivan; Meredith, Fiona M.; Muller, Frank; Nicolson, Marianne; Dahal, Lekh Nath; Abu-Eid, Rasha; Rajpara, Sanjay; Barker, Robert Norman; et al. (Frontiers in Immunology, 2022)
Malignant melanoma is an aggressive form of cancer, which can be treated with anti-CTLA-4 and anti-PD-1 checkpoint inhibitor antibodies but while anti-CTLA-4 antibodies have clear benefits for some patients with melanoma, productive responses are difficult to predict and often associated with serious immune related adverse events. Antibodies specific to CTLA-4 bind two major isoforms of CTLA-4 in humans, the receptor isoform and a second naturally secretable, soluble isoform - sCTLA-4. The primary aim here was to examine the effect of selectively blocking the function of sCTLA-4 on in vitro immune responses from volunteer healthy or melanoma patient PBMC samples. Addition of recombinant sCTLA-4 to healthy PBMC samples demonstrated sCTLA-4 to have immunosuppressive capacity comparable to recombinant CTLA4-Ig, partially reversible upon antibody blockade. Further, we identified a mechanistic relationship where melanoma patient TGFb2 serum levels correlated with sCTLA-4 levels and provided the basis for a novel protocol to enhance sCTLA-4 production and secretion by T cells with TGFb2. Finally, a comparison of selective antibody blockade of sCTLA-4 demonstrated that both healthy and melanoma patient effector cytokine responses can be significantly increased. Overall, the data support the notion that sCTLA-4 is a contributory factor in cancer immune evasion.